Lattice Boltzmann phase field simulations of droplet slicing. (28th April 2021) - Lu, Zeying; Liu, Fengjiao; Liu, Xijian; Zhang, Lijuan; Yuan, Haikuan; Lu, Jie; Derksen, Jos J.
Abstract: We have performed two‐ and three‐dimensional phase field simulations using the lattice‐Boltzmann method of liquid drops rising through a continuous phase liquid under the influence of buoyancy. In their upward motion, the drops encounter a knife that is placed with the purpose of slicing the drops in two. A range of scenarios has been observed when the drop hits the knife and it has been investigated how the type of scenario depends on the dimensionless parameters governing the motion and slicing of the drop: the Eötvös number, the Morton number, and the ratio of the droplet size and the width of the knife. We studied symmetric and asymmetric encounters between drop and knife and kept track of the size distribution of the resulting fragments.